การศึกษาความสูญเสียรายได้ของภาครัฐจากนิติกรรมอำพราง เพื่อการครอบครองอสังหาริมทรัพย์ของคนต่างด้าว STUDY OF THE LOSS OF REVENUE TO THE GOVERNMENT DUE TO FOREIGN ACQUISITION OF THAILAND PROPERTY BY NOMINEES - โกสลากร เพิ่มพูนวิวัฒน์ ชมพูนุท; เชยจิตร รัชพันธุ์; ธนานุภาพพันธุ์ อังคณา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2017)
บทคัดย่อ การวิจัยเรื่องการศึกษาความสูญเสียรายได้ของภาครัฐจากนิติกรรมอำพรางเพื่อการครอบครองอสังหาริมทรัพย์ของคนต่างด้าว มีวัตถุประสงค์ของการวิจัยเพื่อศึกษาความสูญเสียรายได้ของภาครัฐ จากนิติกรรมอำพรางเพื่อการครอบครองอสังหาริมทรัพย์ของคนต่างด้าว โดยใช้การสนทนากลุ่มและสัมภาษณ์เชิงลึกเจาะจง กลุ่มตัวอย่างที่มีประสบการณ์และความรู้เกี่ยวกับการทำนิติกรรมอำพรางคนต่างด้าว ผลการวิจัยพบว่าเส้นทางการทำนิติกรรมอำพรางเพื่อการครอบครองอสังหาริมทรัพย์ของคนต่างด้าวเริ่มจากการจัดตั้งบริษัทต่างด้าวขึ้นในต่างประเทศที่ไม่มีกฎหมายให้เปิดเผยข้อมูล และจัดหาผู้ซื้อต่างด้าวที่ต้องการซื้ออสังหาริมทรัพย์ในประเทศไทย โดยให้คนต่างด้าวซื้อหุ้นในบริษัทดังกล่าวต่อมาจะทำการซื้อที่ดินในประเทศไทยโดยการถือหุ้นแบบอำพรางในบริษัทพัฒนาอสังหาริมทรัพย์ของไทยที่เป็นนอมินีต่างด้าว เพื่อให้ต่างด้าวสามารถซื้อที่ดินในประเทศไทยได้อย่างถูกต้องตามกฎหมายและมีอำนาจในการบริหารบริษัทไทย จากการศึกษาเส้นทางการทำนิติกรรมอำพรางของคนต่างด้าว สามารถแบ่งรายได้ของรัฐที่สูญเสียไปได้เป็นการสูญเสียรายได้ของรัฐบาลกลางและรัฐบาลท้องถิ่น โดยรายได้ที่สูญเสียไปของรัฐบาลกลางจัดเก็บโดยหน่วยงานกรมสรรพากรเกิดจากภาษีที่เกี่ยวข้องกับการขายอสังหาริมทรัพย์ ได้แก่ ภาษีอากรแสตมป์ ภาษีธุรกิจเฉพาะ ภาษีเงินได้นิติบุคคล และภาษีที่เกี่ยวกับการให้คำปรึกษาและการคุมงานก่อสร้าง ได้แก่ ภาษีมูลค่าเพิ่ม รวมถึงค่าธรรมเนียมการโอนของกรมที่ดิน ส่วนรายได้ของรัฐบาลท้องถิ่นที่สูญเสียไปจากภาษีที่เกี่ยวข้องกับการเช่าอสังหาริมทรัพย์ ได้แก่ ภาษีโรงเรือนและที่ดิน Abstract The purpose of the study of the loss of government revenue from hidden transactions for possession of alien’s real estate was to study the loss of government revenue from hidden transactions for possession of alien’s real estate, using focus groups and in-depth interviews from those who had experience and knowledge about hidden transactions of the aliens. The results showed that the path to hidden transactions for real estate business of aliens begins with the setting up of a company in a foreign country where there was no law to disclose information and supply to foreign buyers who wanted to buy real estate in Thailand and given aliens to eventually buy stock in those companies. The study of the path of hidden transactions aliens in Thailand could be divided into the loss of revenue or income generated by the central government and by the local government. The loss of revenue of government impose by The Revenue Department occurred from taxes related to the sale of real estate taxes, including stamp duty, specific business tax, corporate income tax the tax on advising and control the construction, VAT, including the transfer fee of Department of lands. For the loss of revenue of local governments, it is related to real estate which involved property tax.